2000
DOI: 10.1034/j.1600-051x.2000.027007513.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced numbers of Langerhans cells and increased HLA‐DR expression in keratinocytes in the oral gingival epithelium of HIV‐infected patients with periodontitis

Abstract: The findings suggest that the oral gingiva in HIV+ patients may be affected by inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
0
23
1
4
Order By: Relevance
“…In the gingivitis samples, no statistically significant difference was observed between HIV+ and HIV− subjects. These results are not in accordance with a previous study 9 that reported a decrease of LC in AIDS (HIV+) subjects. However, all HIV+ individuals in the present study were using HAART, with a low viral load, and, consequently, showed less direct aggression by LC.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the gingivitis samples, no statistically significant difference was observed between HIV+ and HIV− subjects. These results are not in accordance with a previous study 9 that reported a decrease of LC in AIDS (HIV+) subjects. However, all HIV+ individuals in the present study were using HAART, with a low viral load, and, consequently, showed less direct aggression by LC.…”
Section: Discussioncontrasting
confidence: 99%
“…6 HIV infection is a modifier factor for periodontal disease, responsible for the depletion of CD4+ T lymphocytes, macrophages and LC. 7,8 As a result of this infection, in HIV+ patients with periodontitis, LC were decreased as compared with HIV− subjects 9 ; moreover, the former showed a significant decrease in major histocompatibility complex class II (MHC-II) expression. 10 Recent reports have not indicated a major severity of periodontal disease in HIV+ patients under treatment with antiretroviral agents.…”
Section: Introductionmentioning
confidence: 99%
“…Langerhans cells, which are important for antigen presentation, have been shown to be depleted in the oral mucosa of HIV-infected persons [26,27]. We hypothesize that restoration of Langerhans cells and CD4 T lymphocytes in the oral mucosa occurring in response to reductions in virus load may allow for a marked improvement of HPV antigen recognition and presentation.…”
Section: Discussionmentioning
confidence: 93%
“…The hyperplastic epithelium expresses human leukocyte antigen-DR (HLA-DR) and interleukin (IL)-8 molecules. [1617] The stimulated keratinocytes with HLA-DR molecules in turn release cytokines that increase the T cell trafficking. IL-8 molecules on the other hand bring about HLA-DR + neutrophil exocytosis into parakeratin layer.…”
Section: Etiopathogenesismentioning
confidence: 99%